2016
DOI: 10.18632/oncotarget.7222
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postoperative radiotherapy for squamous cell cancer of the breast in a surveillance epidemiology and end results population-based study

Abstract: The therapeutic value of postoperative radiotherapy (RT) for squamous cell cancer of the breast (SCCB) is unclear. This retrospective study used a population-based national registry to determine the impact of postoperative RT on survival of women with SCCB. The Surveillance Epidemiology and End Results (SEER) database was used to identify females with SCCB who underwent primary surgical resection from 1973 to 2012. Kaplan–Meier survival analysis and Cox regression proportional hazard methods were used to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Two studies [16, 17] reported no benefit of RT on OS, but the small sample sizes in these studies limited their statistical power. Using the SEER database, Wu et al [18] reported that RT was significantly associated with improved OS but not cancer-specific survival, which is difficult to explain. Furthermore, they reported that RT was significantly associated with improved CSS in stage II SCC patients, but the analysis was not adjusted for ER, PR or HER2.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies [16, 17] reported no benefit of RT on OS, but the small sample sizes in these studies limited their statistical power. Using the SEER database, Wu et al [18] reported that RT was significantly associated with improved OS but not cancer-specific survival, which is difficult to explain. Furthermore, they reported that RT was significantly associated with improved CSS in stage II SCC patients, but the analysis was not adjusted for ER, PR or HER2.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that adjuvant radiotherapy following BCS simply provided no significant benefit on OS in patients with PSCC, deviating away from the standard management of more common breast tumours although that may be due to the small sample size ( 129 ). However, Wu et al found that adjuvant radiotherapy had a significant association with improved overall survival in patients with PSCC particularly Stage II tumour and PN0 ( 130 ).…”
Section: Primary Squamous Cell Carcinoma (Pscc)mentioning
confidence: 99%
“…The advantage of revised algorithm is to provide a quantitative index, either lethal frequency or average life, in order to imply the whole survival rate curve under any specific circumstance if and only if the estimated exponential function can properly fit the original data. Therefore, the revised algorithm based on the Taylor series expansion provided the accurate prediction of (i) the survival rate of breast cancer patients, (ii) effectiveness verification of radiotherapy for colon and rectum cancer patients [7, 16], and (iii) re-evaluation of the disease progression for patients of both genders reported by other researchers [17].…”
Section: Discussionmentioning
confidence: 99%
“…Chuang et al investigated the survival rate for breast cancer patients at N1 stage from the cancer registry data bank and revealed a higher survival rate of patients undergone radiotherapy treatment, as compared to those who did not [6]. Wu et al analyzed the data of breast cancer patients from 1973 to 2012 and reported that radiotherapy improved both cause-specific survival (CSS) and overall survival (OS) of patients that underwent the respective surgical operation [7].…”
Section: Introductionmentioning
confidence: 99%